2011
DOI: 10.1080/0144929x.2011.582147
|View full text |Cite
|
Sign up to set email alerts
|

Safe use of symbols in handover documentation for medical teams

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractConcern has been reported about the safe use of medical abbreviations in documents such as handover sheets and medical notes, especially when information is being communicated between staff of different specialties (BBC, 2008, Sheppard et al, 2008. This paper describes a study to investigate whether the use of symbols in handover documentation that is shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…While effective teamwork is considered one of the ways to improve communication and reduce the number of errors, the majority of communication breakdowns occur in verbal communication when patients are being transferred among clinical staff [27]: a practice recognised as a frequent activity at meetings [21], a regular outcome of an MDT discussion, and an acknowledged challenge for researchers in this area [10,27]. Moreover, inadequate medical record-keeping is known to threaten health care quality especially with respect to coordination and continuity of care, decision-making capacity and accountability [32].…”
Section: Introductionmentioning
confidence: 99%
“…While effective teamwork is considered one of the ways to improve communication and reduce the number of errors, the majority of communication breakdowns occur in verbal communication when patients are being transferred among clinical staff [27]: a practice recognised as a frequent activity at meetings [21], a regular outcome of an MDT discussion, and an acknowledged challenge for researchers in this area [10,27]. Moreover, inadequate medical record-keeping is known to threaten health care quality especially with respect to coordination and continuity of care, decision-making capacity and accountability [32].…”
Section: Introductionmentioning
confidence: 99%
“…This seems not to be the case in handovers. Symbols such as "∆", "Ø" were shown to have no unique meaning across handover documents [38]. The authors concluded that an unambiguous set of symbols needed to be defined.…”
Section: Cognitive Maps As Alternatives To Checklist-like Presentatiomentioning
confidence: 99%
“…Although the issue of capturing information during discussion is not discussed directly, several of the papers in this issue refer to the importance of records from team meetings, namely Frykholm and Groth (2011), Meum and Ellingsen (2011), Napolitano et al (2011), without stating the form that those records might take. Galliers et al (2011) prompt consideration of the potential for symbols to be considered in the development of electronic records. That is, the rather vexed issue of how much standardisation is appropriate is raised.…”
Section: Medical Team Meetings: Utilising Technology To Enhance Commumentioning
confidence: 99%